Sistem Pendukung Keputusan Pemilihan Pasta Gigi Terbaik untuk Gigi Berlubang dengan Metode PSI - Widyana, Silva; Siregar, Filzah Naura; Putri, Nurma Wadda; Audi, Femy Ines; Hartama, Dedy (Journal of Information System Research (JOSH), 2025)
Tooth decay, or caries, is a common dental health problem that can have a serious impact on quality of life. This study aims to evaluate the effectiveness of various brands of toothpaste in the prevention and treatment of tooth decay. The methods used included analysis of active ingredients, laboratory tests, and consumer surveys. The toothpastes analyzed included products containing fluoride, calcium phosphate, and xylitol. Laboratory tests were conducted to assess each toothpaste's ability to reduce plaque, inhibit bacterial growth, and support tooth enamel remineralization. Consumer surveys collected data on user experiences and preferences. Based on the results of the analysis using the Preference Selection Index (PSI) method, it can be concluded that Pepsodent (A1) is the best alternative among the toothpaste products evaluated. Pepsodent obtained the highest preference score of 0.824, indicating that this product best suits consumer preferences and needs in addressing cavities. The results of the study show that toothpastes with high fluoride content, such as sodium fluoride and stannous fluoride, are significantly more effective in reducing the risk of caries than other products. In addition, toothpastes containing calcium phosphate show good ability to repair damaged enamel. Conversely, products marketed as “natural” are often less effective in preventing caries. This study provides important insights for consumers in choosing the right toothpaste, especially for individuals at high risk of cavities. These findings can also serve as a reference for manufacturers in developing more effective and safer products for dental health.